In Vitro Effect Of Cow Urine Distillate And Its Synergistic Action With Aqueous Polyherbal Extract On Lymphoblastogenesis In Commercial Layer Chicks - Jivani, Bhavisha M.; Fefar, D.T.; Joshi, B.P.; Ghodasara, D.J.; Patel, Nikita J.; Ghodasara , Priya D. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present investigation was undertaken to study in vitro effect of cow urine distillate and its synergistic action with aqueous polyherbal extract containing Ocimum sanctum (Tulsi), Tinospora cordifolia (Guduchi) and Withania somnifera (Ashwagandha) on lymphoblastogenesis in commercial layer chicks. A total of 270, day old BV-300 layer chicks were randomly divided into nine groups comprising 30 chicks in each group. Group I served as negative control without administration of any treatment except plain water ad libitum. Groups II and III served as positive treatment control groups and were administered with IBD intermediate vaccine and cyclophosphamide as immunosuppressive agents respectively. The remaining treatment groups IV to IX were given either cow urine distillate alone or in combination with aqueous polyherbal extract along with intermediate IBD vaccine and cyclophosphamide. Six birds from each experimental group were sacrificed on day 0, 15, 30, 45 and 60 for collection of materials for lymphoblastogenesis study. The assay revealed significant decrease (P<0.05) in T-cell blastogenesis in group III and B-cell blastogenesis in groups II and III as compared to group I on 30th and 45th day of experiment. There was significant increase (P<0.05) in T-cell and B-cell blastogenesis in groups IV and V as compared to group I, in groups VI and VII as compared to group II and in groups VIII and IX as compared to group III on 30th, 45th and 60th day of experiment. These results suggested the potent humoral and cell mediated immune response of cow urine distillate and its combination with polyherbal extract in layer chicks.